Silencing Dissent: Surveillance and Police Actions on University Campuses during Pro-Palestinian Protests - Monahan, Torin (Surveillance & Society, 2025)
This paper analyzes the relationship between surveillance, violence, and dissent on university campuses in the United States. With a focus on administrative and police responses to pro-Palestinian protesters in particular, I show how surveillance facilitates selective, targeted discipline of students and faculty members expressing pro-Palestinian positions. I explore these dynamics with Colombia University’s police crackdown on protesters; University of California, Los Angeles’s tolerance for terror inflicted by vigilante counterprotesters; and the broader punishment and dismissal of professors voicing criticism of Israel’s war in Gaza. Considered as a whole, these examples reveal a larger cultural landscape that constructs pro-Palestinian groups as fundamentally dangerous, terrorist, and intolerant. Anti-Palestinian violence should be an expected outcome from such an ideological position. The examples also show how campus surveillance practices have shifted to emphasize anticipatory and reactive modalities. In the anticipatory register, surveillance is mobilized as a counterinsurgency tool for the preemptive interruption of pro-Palestinian speech; in the reactive register, surveillance is deployed to punish and terrorize individuals for their expressions of dissent. The reactive modality effectively folds into the anticipatory one by serving as a warning to others and exerting a chilling effect on future campus protests. I argue that universities extend racialized state violence through their surveillance practices and that they remain key players in the maintenance of the racial order.